The Impact of Digital-Based Learning on Learning Concentration and Fundamental Motor Skills in Physical Education at The Junior High School Level - Nadia Izati Natasya; Asep Sumpena; Sufyar Mudjianto (Universitas Negeri Semarang, 2025)
This study examines how Digital Based learning (DBL) influences learning concentration and fundamental motorskills (FMS) among Junior High School students in physical education. This study was designed using a one-group pre-experimental model with pre-tests and post-tests, consisting of 46 eighth-grade students at Junior High School 1 Ciparay. The intruments used in study were a fundamental motorskills assessment and a learning concentration test. The results of this single-group pre-experimental (pre-test-post-test) study, involving 46 eighth-grade boys and girls junior high school students, showed different findings between the variables of learning concentration and Fundamental Motor Skills (FMS). Data analysis, including the Wilcoxon Signed-Rank Test, showed that the Digital-Based Learning (DBL) intervention significantly improved students' learning concentration, with a p < 0.001 value and a Z value of –5.8572. The ranking results showed that almost all students (45 out of 46) experienced an increase in their learning concentration3. Conversely, for the FMS variable, the DBL intervention did not show a significant difference between the pre-test and post-test, resulting in a p = 0.240 (> 0.05) and a Z value of –1.1744. This condition is reinforced by the fact that the number of students who experienced a decrease in FMS scores (23 students) was greater than those who experienced an increase (21 students), indicating that the DBL treatment did not have a significant positive effect on basic motor skills. This sugests that DBL can effectively support cognitive learning aspects. However, DBL alone cannot substitute direct physical activity in develoving fundamental motorskills.